Hypermethylated SHOX2 in circulating cell-free DNA post renal cell carcinoma surgery as TNM-independent biomarker for recurrence risk. - Büttner, Thomas; Zarbl, Romina; Krausewitz, Philipp; Strieth, Sebastian; Kristiansen, Glen; Eckstein, Markus; Ralser, Damian J.; Hölzel, Michael; Ritter, Manuel; Ellinger, Jörg; Dietrich, Dimo; Klümper, Niklas (American Journal of Translational Research, 2024)
INTRODUCTION: Adjuvant immune checkpoint inhibitor trials in renal cell carcinoma (RCC) call for improved recurrence risk stratification. Due to limitations of circulating tumor DNA (ctDNA) use in RCC, the use of hypermethylated SHOX2 gene (mSHOX2) in circulating cell-free DNA is explored as a surrogate marker for identifying high-risk patients after RCC surgery. METHODS: Liquid biopsies were collected post-surgery from 45 RCC patients (mean duration 4.3 days). Real-time polymerase chain reaction was used to analyze SHOX2 methylation in circulating cell-free DNA. Patients were categorized as mSHOX2 positive or negative by cut-off. Metastasis-free survival (MFS), cancer-specific survival (CSS), and overall survival (OS) were assessed using Cox regression and Log-rank analyses (median follow-up time: 60 months). RESULTS: 17 patients were mSHOX2 positive, showing unfavorable OS/CSS (Log-rank P = 0.004 and 0.02) and nearly 6-fold higher recurrence risk (hazard ratio 5.89, 95% CI 1.46-23.8). Multivariable Cox analysis confirmed mSHOX2 as an independent recurrence risk factor, disregarding TNM-based stratification. CONCLUSIONS: mSHOX2 effectively identifies high-risk RCC patients post-surgery, indicating minimal residual disease. This easy to implement biomarker has potential for guiding of adjuvant therapy decisions.
EVALuna2:567881